Hubungan Pengetahuan Manajemen Laktasi dengan Pemberian ASI Eksklusif pada Ibu Menyusui: Relationship in Lactation Management with Exclusive Breastfeeding on Nursing Mothers - Melisa Frisilia; Egha Handriani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Lactation management is all efforts to help mothers succeed in breastfeeding their babies. Exclusive breastfeeding is giving only breast milk to the baby and not giving the baby any other food or drink. The implementation of midwifery activities as the spearhead of the implementation of the MCH program shows that, in general, the quality of the implementation of midwifery activities, including Antenatal Care services, is still low. This study aims to know the relationship between lactation management with exclusive breastfeeding in nursing mothers. The design method in this study is correlational research. The method used in this study uses secondary data derived from several research journals, namely, Hilarius Holan Woja et al. (2018), Yovan Hendrik, Elise Putri (2016), Herry, Evi Nurafiah (2020). Results of the analysis of the 3 (three) study obtained a significant value = 0.006 (p-value ≤ 0.05. There is a relationship between knowledge of lactation management and exclusive breastfeeding for breastfeeding mothers.